2021
DOI: 10.1101/2021.06.20.21259212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential environmental transmission routes of SARS-CoV-2 inside a large meat processing plant experiencing COVID-19 clusters

Abstract: Worldwide exceptionally many COVID-19 clusters were observed in meat processing plants. Many contributing factors, promoting transmission, were suggested, including climate conditions in cooled production rooms favorable for environmental transmission but actual sampling studies are lacking. We aimed to assess SARS-CoV-2 contamination of air and surfaces to gain insight in potential environmental transmission in a large Dutch meat processing plant experiencing COVID-19 clusters.We performed SARS-CoV-2 screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The cutting and deboning areas contained 21% and 50% of the positive SARS-CoV-2 tests among the employees, respectively. Moreover, 3 out of 22 surface samples in productive sections and 3 out of 17 samples in non-productive areas demonstrated active presence of SARS-CoV-2 on high-touch tools in slaughterhouses (39). It was also revealed that mean indoor air temperature was around 6 °C in MPPs.…”
Section: Food Safety and Covid-19 Transmission In Slaughterhousesmentioning
confidence: 91%
See 2 more Smart Citations
“…The cutting and deboning areas contained 21% and 50% of the positive SARS-CoV-2 tests among the employees, respectively. Moreover, 3 out of 22 surface samples in productive sections and 3 out of 17 samples in non-productive areas demonstrated active presence of SARS-CoV-2 on high-touch tools in slaughterhouses (39). It was also revealed that mean indoor air temperature was around 6 °C in MPPs.…”
Section: Food Safety and Covid-19 Transmission In Slaughterhousesmentioning
confidence: 91%
“…The majority of infected employees were mainly from ethnic minority workers and migrants (38). About 40% (66 employees) of infected people consisted of Romanian and Polish workers in pig processing facilities in Netherlands (39). The cutting and deboning areas contained 21% and 50% of the positive SARS-CoV-2 tests among the employees, respectively.…”
Section: Food Safety and Covid-19 Transmission In Slaughterhousesmentioning
confidence: 99%
See 1 more Smart Citation